Pemilihan Tim Bulutangkis Menggunakan Metode Fuzzy Tsukamoto dan AHP-SAW - Randi Pratama Nugraha; Rekyan Regasari Mardi Putri; Lailil Muflikhah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Badminton Activity Unit Universitas Brawijaya is a unit that accommodates students who have interest and talent of badminton sport. It also has to hold selection for badminton athletes who enter through the scholarship path. Those athletes who pass the selection will be the candidates with the athletes in the unit into a team as the representatives of Universitas Brawijaya in certain competition. In selecting process, the candidates need to pass variety of criteria of qualificationt, they are the power of punch, physical stability, movement agility, speed, offense, defense, and readiness. Selection will be conducted using Fuzzy tsukamoto and AHP-SAW method. The Fuzzy Tsukamoto method is used to calculate the number of exercises a player should follow, then the number of these exercises will be used to get the player's readiness score. While the AHP-SAW method is used to determine the weight of each category of matches and the player's rank. The player who has the highest ranking will be selected to be the player candidate in the team. After implementation and testing, the result of single men category correlation is 0.839753, single women is 0.75736, men's double is 0.99079, female double is 0.98921, male tiriple is 0.99886, and triple women is 0.989426. From these results it can be concluded that the results of program and coach decisions are in line and have a positive correlation value and very strong.